The effect of ECN on short TCP sessions - M. Kadhum, Mohammed; Hassan, Suhaidi (IEEE Computer Society, 2007)
Explicit Congestion Notification (ECN) is a method for informing the sender about the network congestion.ECN activation on gateways marks packets instead of dropping them thus lead to faster congestion signal propagation and good network utilization. ECN mechanism does not require generation of additional traffic at the router and can be implemented in the data path of routers. In this paper, we use ns2.29 to investigate the effect of ECN on short TCP sessions using Random Early Detection (RED) gateways.We evaluate the effect of a number of parameters, including buffer size, window size, increase/decrease parameters, size of transfer and RED parameters. We verify that the use of ECN for a slightly big number of short TCP sessions sharing one bottleneck can improve the throughput with fairly less delay.